MEMBANGUN PERILAKU KEUANGAN MELALUI LITERASI, SIKAP, DAN KEYAKINAN DIRI FINANSIAL MAHASISWA STIE CIPUTRA MAKASSAR - Tricia Natalie Josephine; Ayuvati Dewita Chandra; Carmenita Ciptomo; Naomi Gabriela Witera; Theophania Laurens; Maichal Maichal (Parsimonia - Jurnal Ekonomi dan Bisnis, 2026)
There is an imbalance between the level of financial literacy and the level of financial inclusion. This study aims to examine the influence of financial education dimensions, namely Financial Literacy (FL), Financial Attitude (FA), and Financial Self-Efficacy (FSE) on the Financial Management Behavior (FMB) of STIE Ciputra Makassar students. This quantitative study used a survey method with a purposive sampling technique, yielding 114 respondents from Management Department students from the 2022, 2023, and 2024 cohorts. Data analysis was performed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) technique via the SmartPLS 4.0 program. Research results indicate that Financial Self-Efficacy (FSE) has a positive and significant influence on Financial Management Behavior students. Conversely, Financial Attitude (FA) and Financial Literacy (FL) were not found to have a significant influence individually on Financial Management Behavior. This finding emphasizes that students’ self-confidence in their ability to manage money is the primary predictor of their financial management behavior. Theoretically, this result reinforces the Theory of Planned Behavior (TPB) framework that perceived behavioral control (Perceived Behavioral Control, represented by FSE) is a more dominant predictor compared to Attitude or Knowledge in the context of financial management. Policy implications suggest that campus financial education programs should be focused more on strengthening self-confidence and practical skills (self-efficacy) rather than just the transfer of basic knowledge. The novelty of this research lies in presenting unique empirical evidence within the STIE Ciputra Makassar environment and using PLS-SEM which is more comprehensive compared to multiple linear regression analysis often used in previous studies.